A BIOMETRICAL STUDY OF HUMAN MANDIBLE IN INDIAN POPULATION FOR SEX DETERMINATION - DR. VINODINI LAKMALA, M.D; DR. RAJASHREE INALA, M.D (International Journal of Pharma and Bio Sciences, 2016)
The biometrical study of the mandible in human remains will help us in identification of age, sex and race of the individual with available broken pieces of mandible pool with accuracy and clarity. A total of 70 (n=70) adult human mandibles belonging to the Indian population were collected for morphological and morphometric features using ramus breadth, symphysis and condyle height, bigonial breadth, weight, volume and density of the mandible. Based on the maximum and minimum ramus breadth 40 samples could be considered as adult male while, 30 as adult female. Statistical analysis data with mean and SD of various parameters of the mandible viz., ramus breadth, symphysis and condyle height, bigonial breadth, weight, volume and density in male and female were 33.04±0.348 and 27.866±0.668, 31.6±0.327 and 27.6±0.444, 61.125±0.591 and 55.5±0.446, 90.675±0.833 and 81.866±0.919, 61.087±0.712 and 40.433±0.518, 39.025±3.908 and 28.9±0.4022, 1.5628±0.029 and 1.373±0.1255 respectively. Therefore, these results indicated that the average values of all the parameters studied were more in male compared to females. In the present study, there was no statistically significant difference between male and females with respect to different variables however, showed higher values in males compared to females. In conclusion, a large study groups and comprehensive assessment of various parameters related to the mandibles may be required for more definitive and confirmatory results.